Can quantitative contrast-enhanced ultrasonography predict cervical tumor response to neoadjuvant chemotherapy?. Issue 11 (November 2016) - Peng, Chuan; Liu, Long-Zhong; Zheng, Wei; Xie, Yan-Jun; Xiong, Yong-Hong; Li, An-Hua; Pei, Xiao-Qing
Highlights: We assessed the clinical value of quantitative CEUS for prediction of cervical tumor perfusion response to NACT. IMAX, RT, and TTP changed significantly after one NACT cycle. Pre-treatment IMAX positively correlated with the absolute and percentage changes in all cervical tumor IMAX after NACT. Pre-treatment IMAX may be predictive of NACT perfusion response in cervical tumor. Abstract: Objective: To evaluate the feasibility of quantitative contrast-enhanced ultrasonography (CEUS) for predicting and assessing cervical tumor response to neoadjuvant chemotherapy (NACT). Methods: Thirty-eight cases with stage IB2 or IIA cervical cancer were studied using CEUS before and after one cycle of NACT. The quantitative CEUS parameters maximum intensity (IMAX), rise time (RT), time to peak (TTP), and mean transit time (MTT) were compared between cervical tumors and myometrium (reference zone) using Sonoliver software. Absolute and relative changes in quantitative CEUS parameters were also compared among complete response, partial response, and non-responsive groups. Correlations between pre-treatment IMAX and changes in quantitative parameters were assessed after one cycle of NACT. Results: There were significant changes in cervical tumor IMAX ( P  < 0.001), RT ( P  < 0.05), and TTP ( P  < 0.05) after one cycle of NACT. According to the Response Evaluation Criteria In Solid Tumors guidelines, the enrollments were divided into complete response, partial response, stable disease and progressive disease groups. There were no significant differences in quantitative CEUS parameters among complete response, partial response, and non-responsive groups ( P   >  0.05). In the stable disease group (n = 17), cervical tumor IMAX, RT, and TTP decreased significantly after NACT ( P  < 0.001). The absolute and percentage changes in IMAX were positively correlated with pre-treatment IMAX in all 38 patients (r = 0.576, P  < 0.001 and r = 0.429, P  < 0.001). Conclusion: Quantitative CEUS analysis can reveal changes in tumor perfusion following NACT. Tumor perfusion values changes likely precede size changes during the NACT course, and pre-treatment IMAX may be a valuable predictor of cervical tumor perfusion response to NACT with a great decrease in IMAX correlated with better perfusion response.